Help Is in Your Blood—Incentive to “Double Altruism” Resolves the Plasma Donation Paradox - Gyuris, Petra; Gáspár, Baksa Gergely; Birkás, Béla; Csókási, Krisztina; Kocsor, Ferenc (Frontiers in Psychology, 2021)
Blood donation is considered one of the purest forms of altruism. Plasma donation, in contrast, despite being a similar process, is mostly a paid activity in which donors are compensated for their contribution to the production of therapeutic preparations. This creates a so-called “plasma paradox”: if remuneration is promised for a socially useful effort, volunteers with altruistic motives might be deterred. At the same time, regular plasma donors who pursue the monetary benefits of donation might drop out if remuneration stops. The same controversy can be caught in the messages of most plasma donation companies as well: they promise a monetary reward, and at the same time highlight the altruistic component of donation. In this study, we tested the assumption that emphasizing the social significance enhances the willingness to donate blood plasma more effectively than either monetary reward or the combination of these two incentives. This had to be rejected, since there was no significant difference between the three scenarios. Furthermore, we also hypothesized that individuals might be more motivated to donate plasma if there is a possibility of offering a monetary reward toward other socially beneficial aims. We found an increased willingness to donate in scenarios enabling “double altruism”, that is, when donating plasma for therapeutic use and transferring their remuneration to non-governmental organizations, is an option. We propose relying on double altruism to resolve the plasma paradox, and suggest that it could serve as a starting point for the development of more optimized means for donor recruitment.